Pemberdayaan Masyarakat Melalui Desain Kapal Fiberglass Untuk Pembuatan Perahu Gutek Bagi Nelayan Desa Taddan - David Indrawan; Arief Syarifuddin; Anauta Lungiding Angga R.; Rendi Darmawansyah; Kholidah Qurrota Ayu Ninah (Pusat Riset dan Inovasi Nasional, 2023)
Madura has the most fisheries potential, because although Madura Island is small, the people mostly live around the coast. In the main Taddan Village, there are lots of people who work as fishermen, who go to sea every day. Many fishermen are also craftsmen of boats for personal use or for sale, where fishermen still use wood when making boats. Many large trees in Taddan Village are no longer visible. For this reason, this research will explain some of the advantages of fiberglass boats and how to design and manufacture them. From the program that researchers will carry out, it is hoped that the community will be able to apply it. This research is also very useful for youth groups whose curiosity is greater. Even though the Karangtaruna are not educated in the world of shipping, they will understand how to make and read ship designs.